Anne Frank's Tales from the secret annex - Frank, Anne, 1929-1945.; Manheim, Ralph, 1907-1992.; Mok, Michel (New York : Bantam Books, 1994)
This compilation is a complete collection of Anne Frank's lesser-known writings--short stories, fables, personal reminiscences and an unfinished novel--composed during her seclusion from the Nazis during World War II. These writings reveal the astonishing range of Anne's wisdom and youthful imagination. An invaluable companion to Diary of a Young Girl.
Fables and short stories: Kitty ; Porter's family ; Eve's dream ; Paula's plane trip ; Kathy Flower girl ; Guardian angel ; Fear ; Wise old dwarf ; Blurry, the explorer ; Fairy ; Rita ; Jackie ; Cady's life -- Personal reminiscences and essays: Do you remember? ; Flea ; Battle of the potatoes ; Villains! ; My first day at the Lyceum ; Lecture in biology ; Geometry lesson ; Roomers or subtenants ; Dreams of movie stardom ; Sunday ; My first article ; Sink of iniquity ; Happiness ; Give ; Who is interesting? ; Why?
Translation of: Verhaaltjes en gebeurtenissen uit het Achterhuis.
"Previously published in part as Tales from the house behind."
Keywords: Frank, Anne, -- 1929-1945.; Jews -- Netherlands; World War, 1939-1945 -- Jews -- Netherlands; Netherlands -- History -- German occupation, 1940-1945.; Short stories